PERKEMBANGAN SEKSUAL SANTRI PADA PESANTREN SINGLE-SEX - Agus Abdul Rahman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2008)
Pesantren (Islamic boarding school) as islamic educational institution in general organizes and designs curriculum that able to avoid its students from sexual behavior that contrast to the islamic values, as well as in pesantren or after graduating from pesantren. One of the effort of pesntren to reach such goal among them are by organizing the relationship between sexs and to separate its students according to the sexs. Students are faced to the situation that different at all with the actual reality. Some aspects are regarded can direct to the social contact between sexs are controlled. The question appears about how the influence of the sexs separation (single sex-pesantren) to the student sexual development, as they coming out from that pesantren and must face the actual reality, which heterogenous, uncontrollabe and different at all with the relaity that experienced in pesantren.